Obstructive salivary gland disorders -A Malaysian patient series - Subha, Sethu Thakachy; Osman, Malina; Narayanan, Prepageran (Georg Thieme Verlag KG, 2024)
Introduction Obstructive salivary gland disease is a frequently encountered clinical entity that can present to various health practitioners. Obstructive sialadenitis can lead to recurrent infections and debilitating quality-of-life issues. Objective There is a paucity of published data regarding obstructive salivary disorders among the multiracial Asian population. The present study aimed to determine the demographic pattern and risk factors of obstructive salivary gland disorders with the goal of better management of this condition. Method A retrospective cross-sectional study was conducted at a tertiary institution over a period of 5 years. Results A total of 256 (9.84 for every 1,000) patients were found to have salivary disorders, 10% of who were diagnosed to have obstructive disorder. Among the obstructive salivary disorders, 76% had sialolithiasis, 19% had recurrent parotitis, and 1 patient had chronic sialadenitis. We observed a small female preponderance for obstructive salivary disorders. This study revealed that smoking is a significant risk factor (p ¼ 0.041; prevalence ratio ¼ 2.54, 95% confidence interval 1.12–5.78), and smokers were 2.5 times more likely to develop obstructive salivary disorders. There was no statistical correlation between the prevalence and other risk factors like infection, dehydration, intake of medications, history of diabetes mellitus, radiotherapy, and autoimmune disorders. Conclusion Our study results demonstrated that the prevalence of obstructive salivary gland disorders was 0.1%. This study provided a better understanding of the prevalence and risk factors of obstructive salivary disorders, which facilitate timely management and improves quality of life.